Mediating role of students’ engagement to their classes - Ahmed Siddiqi (AAOU Journal, 2018)
Purpose - The purpose of this paper is to establish the mediating role of students’ engagement to their classes, for the conventional relationship between teachers’ efforts and students’ development, for a better understanding of the instruction-based classroom learning. Design/methodology/approach - The investigation is made using a mult-istage-stratified-systematic sample of 500 students from business and engineering schools with an almost equal representation of both the genders and the type of schools’ ownership. A structural equation modeling is used for this mediation analysis. Findings - The mediating role of students’ engagement is identically established both for business and engineering schools and for both genders. However, in public sector universities, this mediation is insignificant. Research limitations/implications - The investigation is limited only to business and engineering schools, and this limitation may conceal some factor(s) more important for other schools. Further, the investigation is reading data from Lahore, a metropolitan, which may hide some factor(s) some appropriate for smaller cities. Originality/value - The data are gathered, analyzed and discussed through the lens of the socio-cultural theory, allowing for a comprehensive understanding to emerge for students’ engagement to their classes.